(untitled) (Educação e Pesquisa, 2020)
Given its increasing importance, society nowadays requires from professionals not only the specific competencies in each discipline but also the universities are demanded to develop the so-called transversal or generic competencies. The objective of this work is to present the trajectory of a certain program intended to provide generic competencies in undergraduate careers in a state-owned Chilean institution, the University of Talca. This trajectory is over 10 years old since it started in 2006, and is expressed in three versions, where the latter is a possible bottom line example for other undergraduate careers and universities interested in adopting an educative model based on the development of competencies. The methodology utilized is a description research based on a review of the official documentation of the University of Talca, and the background collected by the authors in their condition of professors in a career of engineering. The results achieved so far show a process of continuous improvement and maturation characterized by a clarification of the concept of competency, a significant reduction in the size of PFF, and an effort to combine it with the competencies of basic and professional training (or in a discipline) of each career. Notwithstanding what is mentioned above, conclusion is that there is still room for significant improvements if the aspiration is to consolidate the program.